2016
DOI: 10.1007/s10463-016-0582-9
|View full text |Cite
|
Sign up to set email alerts
|

Limiting behaviour of Fréchet means in the space of phylogenetic trees

Abstract: As demonstrated in our previous work on T4, the space of phylogenetic trees with four leaves, the global, as well as the local, topological structure of the space plays an important role in the non-classical limiting behaviour of the sample Fréchet means of a probability distribution on T4. Nevertheless, the techniques used in that paper were specific to T4 and cannot be adapted to analyse Fréchet means in the space Tm of phylogenetic trees with m( 5) leaves. To investigate the latter, this paper first studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 19 publications
(85 reference statements)
4
51
0
Order By: Relevance
“…For instance, Feragen et al (2011) developed an approach that avoids both the planar embedding and fixed-leaf-set problems, and Nye (2011) invented an analogue of principal component analysis for phylogenetic trees. Hotz et al (2013), followed by Barden, Le and Owen (2013, 2014), investigated surprising nonstandard central limit theory in phylogenetic tree spaces. Finally, an analysis [Wright et al (2013)] of a different, and smaller, set of MRA brain artery images also found a connection between vessel length and healthy aging.…”
Section: Brain Artery Treesmentioning
confidence: 99%
“…For instance, Feragen et al (2011) developed an approach that avoids both the planar embedding and fixed-leaf-set problems, and Nye (2011) invented an analogue of principal component analysis for phylogenetic trees. Hotz et al (2013), followed by Barden, Le and Owen (2013, 2014), investigated surprising nonstandard central limit theory in phylogenetic tree spaces. Finally, an analysis [Wright et al (2013)] of a different, and smaller, set of MRA brain artery images also found a connection between vessel length and healthy aging.…”
Section: Brain Artery Treesmentioning
confidence: 99%
“…Although we do not make it explicit, in view of our previous results for T m+2 and the comments in [15], our interest in this paper is primarily in the case that x * lies in a stratum of local co-dimension at least two. The results, when restricted to a locally top-dimensional or co-dimension one stratum, do generalise those for tree spaces in [3] although the approach here is necessarily more complex in order to encompass all cases.…”
Section: Introductionmentioning
confidence: 68%
“…With the description of the carrier, as well as the results on the support, of a geodesic in the previous section, we are now in a position to derive and analyse its initial tangent vector, or equivalently log x * (x) for x * ∈ σ = O(E). As in [2,3] for the space of trees, our analysis will mainly involve a modified version of the logarithm map. For this, since the tangent cones at various points in σ are all parallel, we may parallel translate them to the cone point o, the origin in R M , to produce a common isometric copy C σ .…”
Section: The Logarithm Mapmentioning
confidence: 99%
See 2 more Smart Citations